(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of the nurse’s managerial work process in the Rapid Test sector of a Basic Health Unit located in the city of Niterói/RJ. Method: experience report of a visit to a Basic Health Unit (BHU) in the rapid testing sector; in which we sought to describe the steps that are performed during the rapid test, the organization that the nursing professional responsible for the sector does in their daily lives, the nurse-patient interaction and what the process is like before and after the exam, as well as how to proceed in positive and negative cases Results and Discussion: The rapid test activity with users of a UBS held in the first half of 2022, had the participation of academics from the 6th period of nursing from the Aurora de Afonso Costa Nursing School (EEAAC) of the University Federal Fluminense (UFF) who participated observing the managerial work process of nurses. Reception in the nursing consultation is an essential moment during the test for the diagnosis of STI, as it requires the professional’s ability to deal with the demands. Conclusion: This experience report made possible a theoretical-practical learning about the organization of a rapid testing sector for STIs, as well as the duties and responsibilities of nurses in this sector.